Surgical Management of Chronic Locked Posterior Dislocation of Shoulder using the Modified McLaughlin Procedure - Naman K Parakh; Abhishek Ashok Sharma; S Krishna Kumar (Journal of Orthopaedic Case Reports)
Introduction: Chronic locked posterior dislocation (CLPD) of the shoulder presents a big challenge to the orthopedic surgeon due to the progressive damage to the glenohumeral articulation and increase in size of the reverse Hill-Sachs lesion (RHSL). Multiple treatment strategies have been postulated depending upon the size of the humeral head defect and the RHSL. Case Report: A 35-year-old Indian male patient presented to our Outpatient Department with complaints of pain and restriction in the range of motion over the right shoulder since suffering an injury over the shoulder 6 months back. Clinical examination revealed a bony restriction particularly in external rotation, flexion, and abduction of the right shoulder. The radiographs were suggestive of CLPD of the right shoulder with a large sized humeral head defect. An magnetic resonance imaging of the right shoulder was done to quantify the defect and reveal the anatomical status of the shoulder joint. After proper planning and workup, the patient was managed surgically with the modified McLaughlin procedure. Proper rehabilitation and regular follow-ups were done and the patient showed significant functional improvement of the right shoulder at 2-year follow-up. Conclusion: The treatment of CLPD varies according to the size of the humeral head defect and the functional demand of the patient. The modified McLaughlin procedure is an excellent option in mild to moderate-sized defects. The results of the procedure are also affected by the delay in treatment since the time of injury.